Time-Course RNAseq Reveals Exserohilum turcicum Effectors and Pathogenicity Determinants - Human, Maria Petronella; Berger, Dave Kenneth; Crampton, Bridget Genevieve (Frontiers in Microbiology, 2020)
Exserohilum turcicum (sexual stage Setosphaeria turcica) is the hemibiotrophic causal agent of northern leaf blight of maize and sorghum. This study aimed to identify the genes involved in host colonization during the biotrophic and necrotrophic phases of infection. It also aimed to identify race-specific differences in gene expression. RNAseq of maize seedlings inoculated with a race 13N or 23N E. turcicum isolate was conducted prior to inoculation and at 2, 5, 7 and 13 days post inoculation (dpi). Biological replicates were pooled per time point for each race and sequenced. A bioinformatics pipeline was used to identify candidate effectors and expression was validated for selected candidates. Fungal biomass was positively correlated with the percentages of E. turcicum reads mapped, which were low at early time points (2 – 7 dpi) with a significant increase at 13 dpi, indicating a lifestyle switch from biotrophy to necrotrophy between 7 and 13 dpi. AVRHt1 is the putative E. turcicum effector recognized by the maize resistance gene Ht1. Consistent with this, AVRHt1 was expressed in planta by race 23N, but transcripts were absent in race 13N. In addition, specific transposable elements were expressed in 23N only. Genes encoding the virulence-associated peptidases leupeptin-inhibiting protein 1 and fungalysin were expressed in planta. Transcriptional profiles of genes involved in secondary metabolite synthesis or cell wall degradation revealed the importance of these genes during late stages of infection (13 dpi). A total of 346 expressed candidate effectors were identified, including Ecp6 and proteins similar to the secreted in xylem (SIX) effectors common to formae speciales of Fusarium oxysporum, SIX13 and SIX5. Expression profiling of Ecp6 and SIX13-like indicated a peak in expression at 5 and 7 dpi compared to 2 and 13 dpi. Sequencing of SIX13-like from diverse isolates of E. turcicum revealed host-specific polymorphisms that were mostly non-synonymous, resulting in two groups of SIX13-like proteins that corresponded to the maize or sorghum origin of each isolate. This study suggests putative mechanisms whereby E. turcicum causes disease. Identification of the candidate effector SIX13-like is consistent with the infection mode of E. turcicum through the xylem of susceptible hosts.